Cost-Effectiveness of Total Colonoscopy in Screening of Colorectal Cancer in Japan - Masau Sekiguchi; Takahisa Matsuda; Naoto Tamai; Taku Sakamoto; Takeshi Nakajima; Yosuke Otake; Yasuo Kakugawa; Yoshitaka Murakami; Yutaka Saito (Gastroenterology Research and Practice)
Introduction. In Japan, the cost-effectiveness of total colonoscopy (TCS) for primary screening of colorectal cancer (CRC) is unclear. We compared the cost of identifying a patient with CRC using two primary screening strategies: TCS (strategy 1) and the immunochemical fecal test (FIT) (strategy 2). Materials and Methods. We retrospectively analyzed the TCS screening database at our institution from February 2004 to August 2010 (strategy 1, 𝑛=15,348) and the Japanese nationwide survey of CRC screening in 2008 (strategy 2, 𝑛=5,267,443). Results. 112 and 6,838 CRC cases were detected in strategies 1 and 2, costing 2,124,000 JPY and 1,629,000 JPY, respectively. The rate of earlier-stage CRC was higher in strategy 1. Conclusions. The cost was higher using TCS as a primary screening procedure. However, the difference was not excessive, and considering the increased rate of detecting earlier CRC, the use of TCS as a primary screening tool may be cost-effective.